2006
DOI: 10.1007/s10350-005-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy in the Elderly: Low Risk, Low Yield in Asymptomatic Patients

Abstract: Colonoscopy can be performed safely in patients aged 80 years and older. However, the diagnostic yield is low, particularly in patients undergoing routine screening or surveillance examinations. Colonoscopy should for the most part be limited to elderly patients with symptoms or specific clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 16 publications
(11 reference statements)
4
55
1
5
Order By: Relevance
“…Arora et al [51] , 2004 110 80+ 97% 1 20% -Syn et al [9] , 2005 225 80+ 56% 11% 25% Yoong et al [52] , complication rate in patients over 80 is low, between 0.2% and 0.6% [11,15] , although it increased with specific comorbid conditions [24] . A large retrospective study reported an overall perforation rate of 0.082% for adults undergoing colonoscopy, with advanced age as a significant predictor [25] .…”
Section: +mentioning
confidence: 98%
See 2 more Smart Citations
“…Arora et al [51] , 2004 110 80+ 97% 1 20% -Syn et al [9] , 2005 225 80+ 56% 11% 25% Yoong et al [52] , complication rate in patients over 80 is low, between 0.2% and 0.6% [11,15] , although it increased with specific comorbid conditions [24] . A large retrospective study reported an overall perforation rate of 0.082% for adults undergoing colonoscopy, with advanced age as a significant predictor [25] .…”
Section: +mentioning
confidence: 98%
“…Numerous studies have confirmed high yields for both screening and diagnostic colonoscopy in elderly patients ( Table 1). The reported yield of CRC in symptomatic elderly patients has ranged from 3.7% to 14.2% [9][10][11][12] . In a study on 200 symptomatic octogenarians, 80% had colonoscopic findings that explained their symptoms [13] .…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been seen that colonoscopy yields a noninfectious diagnosis more oft en than upper endoscopy (170)(171)(172). A review of 18 primary studies looking at the diagnostic value of colonoscopy in patients with chronic diarrhea, as well as a review of nine published guidelines provides the basis for a colonoscopy recommendation in such patients ( 165,167,168,(173)(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186).…”
Section: Th E Evidence Does Not Support Empiric Anti-microbial Therapymentioning
confidence: 99%
“…In fact, colorectal cancer, vascular and diverticular diseases are more common among the elderly [111,112] . Even though the prevalence of neoplastic lesions increases with age, the diagnostic yield of a screening colonoscopy among the elderly (aged ≥ 80 years), who have a short life expectancy, is low [113] . This indicates the limits of screening procedures.…”
Section: Elderly Patientsmentioning
confidence: 99%